Breath Analysis Using a Time-of-Flight Camera and Pressure Belts - Zalud, Ludek; Kotova, Marketa; Kocmanová, Petra; Dobsak, Petr; Kolarova, Jana (Artificial organs, 2016)
The proper way of breathing is important for everyone. Healthy people often do not follow respiration until breathing problems start-during stress or during sport activity in physiological cases. More serious cases are stroke, injury, or surgery of the chest and others. So, learning to breathe correctly and/or breathing diagnosis is considerable for many reasons. Two novel methods of breath analysis suitable for diagnostics and rehabilitation are presented. The first technique utilizes pressure belts fastened to the patient's belly and chest, and the second method relies on a SwissRanger SR-4000 time-of-flight camera. The measurement principles are described together with the advantages and disadvantages of the applied techniques. The SwissRanger camera depth calibration is proposed to facilitate better results during the breath analysis. The methods are tested on a group of students to provide a comparison of their individual performances. As it was demonstrated, presented methods proved to work reliably. The method based on time-of-flight camera seems to be more suitable for diagnosis, while the method based on pressure belts is more suitable for rehabilitation and biofeedback applications.
Keywords: Young Adult; Male; Video Recording; mladý dospělý; dechové testy; Equipment Design; Adult; dospělí; mužské pohlaví; audiovizuální záznam; kalibrace; design vybavení; Breath Tests; Respiration; lidé; ženské pohlaví; Humans; Pressure; tlak; Female; Calibration; dýchání